The Flowing Bowl : A Treatise on Drinks of All Kinds and of All Periods, Interspersed with Sundry Anecdotes and Reminiscences - Spencer, Edward, 1844-1910 (Salt Lake City, UT : Project Gutenberg, 2018)
"The Flowing Bowl" by Edward Spencer is a treatise on drinks of all kinds, written in the early 20th century. The work combines historical anecdotes and recipes, celebrating the culture of drinking through the ages. It reflects on how alcohol has been viewed and enjoyed in various societies, providing an insightful commentary on the connection between beverages and social practices. At the start of the book, the author presents his preface, humorously touching upon motivations for compiling this collection. He emphasizes the importance of moderation in drinking while revealing that much of the content is a compilation of quotes and anecdotes from classical and historical sources. The opening sets the stage for a discussion of drinking customs, opening with reflections on the ancient world's fondness for beverages and their habits, leading naturally into an exploration of notable figures and their drinking behaviors. Spencer's engaging style invites readers to consider the intersections of culture, morality, and enjoyment associated with drinking throughout history. (This is an automatically generated summary.)
Release date is 2018-05-18
E-text prepared by ellinora, RichardW, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Liquors; Wine and wine making; Alcoholic beverages